Analysis of Corneal Astigmatism after Clear Corneal Phacoemulsification : A Prospective Study - Agrawal, Nisha; Agarwal, Lalit; Yadav, Reena; Kumari, Archana; Singh, Kinsuk; Baral, Dharanidhar (Birat Journal of Health Sciences, 2020)
Introduction: With the evolution of cataract surgery over the past years and increasing patient demand for spectacle independence, today cataract surgery is moreover a refractive surgery. Surgically induced astigmatism (SIA) hinders post-operative refractive precision by changing the refractive power of cornea. Objectives: To calculate and compare SIA and postoperative spherical equivalent (SE) among eyes undergoing phacoemulsification performed via superior and temporal approach. Methodology: A longitudinal prospective observational study was conducted in a tertiary eye care center. 200 consecutive patients who underwent 2.8mm clear corneal phacoemulsification were allocated in Group A (Superior) and Group B (Temporal) in equal numbers by random lotiery method. Patients with any corneal pathology, glaucoma, retina or macular diseases, with previous history of trauma or ocular surgery were excluded. Preoperative astigmatism, postoperative astigmatism and postoperative SE were calculated at 6weeks follow-up. SIA was calculated using vector analysis software version 2.1 given by Dr Sawhney. Results Eighty patients of group A and 99 patients of Group B were included in the analysis. Preoperative keratometry and astigmatism was comparable between the two groups. Postopera tive astigmatism was significantly lower in temporal incision (0.75± 0.58) group than in superior incision group (1.2±0.71). SIA in-group A was 0.43D and in group B was 0.18D. SE was found to be significantly lower in temporal incision (p<0.01) group. Conclusion Temporal incision is astigmatically more neutral and has betier refractive precision than superior incision clear corneal phacoemulsification.